2018
DOI: 10.3390/act7010007
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and Control of Ionic Electroactive Polymer Actuators under Varying Humidity Conditions

Abstract: In this work, we address the problem of position control of ionic electroactive polymer soft actuators under varying relative humidity conditions. The impact of humidity on the actuation performance of ionic actuators is studied through frequency response and impedance spectroscopy analysis. Considering the uncertain performance of the actuator under varying humidity conditions, an adaptable model using the neural network method is developed. The model uses relative humidity magnitude as one of the model param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…It has been shown that the actuator under investigation may be highly sensitive to humidity fluctuations [25,52,53]. As this paper is not concerned in the impact of humidity on actuators model, the actuator was driven in a special chamber filled with clean nitrogen environment, from which traces of H 2 O and O 2 were almost completely removed (0.01 ppm and 0.2 ppm, respectively).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the actuator under investigation may be highly sensitive to humidity fluctuations [25,52,53]. As this paper is not concerned in the impact of humidity on actuators model, the actuator was driven in a special chamber filled with clean nitrogen environment, from which traces of H 2 O and O 2 were almost completely removed (0.01 ppm and 0.2 ppm, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…From the perspective of applications, such behavior is rather considered as a material drawback that hinders the performance and has to be compensated by proper control. So far IPMC actuators with nanoporous carbon electrodes have been successfully controlled using system identification and model inversion [23,24], or model predictive control based scheme [25], however, in this work we focus on more advanced methods exploiting fractional-order (FO) calculus.…”
Section: Introductionmentioning
confidence: 99%
“…Such IPNs use one polymer network as ion conducting material and a second polymer network to provide the required mechanical properties. Newer research has proposed ink-jet printing of PEDOT:PSS on IPN networks for mass production of air-operating artificial muscles and supercapacitors (Nakshatharan et al, 2018). Other findings provided fast and durable CP actuators using graphene and a percolation network of silver nanowires to enhance the conductivity of the PEDOT:PSS electrodes (Park et al, 2018).…”
Section: Types Of Ionic Eapmentioning
confidence: 99%
“…The most commonly known IEAP is the ionic polymermetal composite (IPMC) which is predominantly used as an actuator. IPMCs are composed of an ionic polymer membrane, typically Nafion, sandwiched between a pair of noble metal electrodes (Nakshatharan et al, 2018;Tamagawa et al, 2019).…”
Section: Types Of Ionic Eapmentioning
confidence: 99%
“…Due to their good learning capability, many neural networks (NNs) have been applied in many linear and nonlinear systems, such as optimal hysteresis modelling methods of magnetic controlled shape memory alloys (MSMAs) [5], control of ionic electroactive polymer actuators [6], predicting the driving force for a multicyclic driving experiment of silicone/ethanol soft composite material actuators [7], and design of a 2-DOF ankle exoskeleton with a bidirectional tendon-driving actuator and a polycentric structure [8]. These NNs take a long time to conduct training and learning of a system.…”
Section: Introductionmentioning
confidence: 99%